Synergetic–Complementary Use of Industrial Solid Wastes to Prepare High-Performance Rapid Repair Mortar - Li, Jingwei; Xu, Dong; Wang, Xujiang; Wang, Kun; Wang, Wenlong (Frontiers in Materials, 2021)
With the vigorous development of infrastructure engineering, there is growing demands for high-performance rapid repair mortar, especially those using environmental-friendly and low-carbon cementitious materials. Hereupon, this work explored an innovative approach for rapid repair mortar preparation using solid waste-based sulfoaluminate cement. A sulfoaluminate cement was first prepared via synergetic-complementary use of industrial solid wastes, and then adopted to prepare rapid repair mortar by proportionally mixing with standard sand and four additives (i.e., polycarboxylate superplasticizer, lithium carbonate, boric acid, and latex powder). The mechanistic analysis indicated that, the four additives comprehensively optimized the mechanical strengths, fluidity, and setting time of rapid repair mortar by adjusting the hydration process of sulfoaluminate cement. The test results showed that, the 2h compressive and flexural strength, and 1d bonding strength of the prepared rapid repair mortar were 32.5 MPa, 9.2 MPa, and 2.01 MPa, respectively, indicating excellent early-age mechanical performance. In addition, the 28d compressive and flexural strengths of the rapid repair mortar reached 71.8 MPa and 17.7 MPa. Finally, a life cycle assessment and economic analysis indicated that this approach achieved environmental-friendly utilization of industrial solid wastes, and cost-effective and energy-saving natures, which supports current trends towards a circular economy and green sustainable development.